Combined education course on nutrition, hand-washing and dental care in primary schools in Yaoundé, Cameroon - Philomina Fankam Yamgai; Guy B. Pouokam; Brice U. Saha Foudjo; Francesca Mazzanti; Joel T. Sando; Chi Samuel; Aristide G. Kamda Silapeux; Elie Fokou; Chiara Frazzoli (Journal of Global Health Reports)
# Background